THE IMPACT OF MEDIA LITERACY AND INFORMATION TECHNOLOGY ON ENGLISH SKILLS - Anvarova , Xurshidabegim (University Research Base, 2025)
The integration of media literacy and information technology (IT) has become a pivotal aspect of language education, particularly in the context of English language acquisition. This paper explores the impact of media literacy and IT on enhancing English skills, such as reading, writing, listening, and speaking. The role of digital platforms, social media, and educational technology is critically examined to understand how they contribute to both traditional and modern English learning approaches. The study highlights the intersection between digital media consumption and language development, emphasizing how effective media literacy can empower learners to navigate and use English in diverse contexts. The findings suggest that while media literacy and IT offer numerous benefits in improving English skills, challenges such as information overload, distractions, and the digital divide must be considered.